Understanding the links between agriculture and health: Agricultural technology and health - Lipton, Michael; Sinha, Saurabh; Blackman, Rachel (International Food Policy Research Institute, 2006)
Research, invention, and adoption of agrotechnology have played an important role in improving human nutrition and health. Agrotechnology has introduced more effective plant breeds (such as high-yielding varieties), enhanced land management techniques (such as terracing), and improved water management tools (such as irrigation). The adoption of these techniques has benefited nutrition, largely through boosting crop productivity, thereby providing employment and income to rural populations and increasing local and global food supplies... for the health needs of small farmers and laborers—as well as poor consumers—to influence research decisions, governments need to develop (1) institutions and incentives to promote such people’s participation and communication with the formal research community; (2) competition among private research providers; and (3) public research in activities that respond to farmers’ needs but are unlikely to attract formal private research.